The birth of the despot : Venice and the Sublime Porte - Valensi, Lucette (Cornell University Press, 1993)
"In an elegant and graceful account of the transformation of European attitudes toward the Ottoman empire during the sixteenth and seventeenth centuries, Lucette Valensi follows the genealogy of the concept of Oriental despotism. The Birth of the Despot examines a crucial moment in the long and ambiguous encounter between the Christian and Islamic worlds: the period after the fall of Constantinople to the Turks, when Venice's pursuit of its commercial and maritime interests brought two powerful protagonists - Venice and the Sublime Porte - face to face. First published in French in 1987, the book is now made available to English readers in Arthur Denner's fluent translation." "Vivaldi's oratorio Juditha Triumphans, in which Judith liberates her besieged town by killing the Turk Holofernes, serves as the organizing metaphor in Valensi's study of how Venice's perceptions of its eastern rival changed. Drawing on the reports that Venice's ambassadors to Constantinople delivered in person before the senate and the doge, the author reflects on the tumultuous events both outside and inside Europe which shaped the continent's political consciousness. Valensi shows how Venice's initial admiration for the sultan and his orderly empire - an admiration reflected in writers as late as Machiavelli - metamorphosed into revulsion at a monstrous tyrant who was to become the model of Montesquieu's Oriental despot."--Jacket